The Effect of Leadership and Teamwork on Employee Turnover and Team Performance - Putri, Alin Rizkiani; Renwarin, Joseph M.J. (Human Capital and Organizations, 2023)
This study aims to investigate the influence of leadership and teamwork on team performance while exploring the potential effects of team turnover. Our methodology involved distributing questionnaires to 60 individuals who met our specific criteria. The data collected was analyzed using the advanced statistical analysis software SPSS 20.0. Our findings indicate that leadership and teamwork are crucial in team performance, with a significant impact observed. Additionally, our research indicates that team turnover does not affect team performance. For a company to achieve optimal success and productivity, it is imperative to thoroughly examine and analyze the influence of leadership and teamwork on team performance and turnover. By doing so, organizations can better understand the underlying factors contributing to these outcomes and make informed decisions to enhance team dynamics and drive positive results.